Earthquake Bond Pricing Model Involving the Inconstant Event Intensity and Maximum Strength - Riza Andrian Ibrahim; Riza Andrian Ibrahim; Herlina Napitupulu; Rose Irnawaty Ibrahim (MDPI, 2024)
Indexed by WOS/ Scopus